The serine protease homolog CLIPA14 modulates the intensity of the immune response in the mosquito Anopheles gambiae - Christophides,GK; Nakhleh,J; Osta,MA (Journal of Biological Chemistry, 2017)
CLIP domain serine protease homologues (cSPHs) are positive and negative regulators of Anopheles gambiae immune responses mediated by the complement-like protein TEP1 against Plasmodium malaria parasites and other microbial infections. We have previously reported that the SPH CLIPA2 is a negative regulator of the TEP1-mediated response by showing that CLIPA2 knockdown (kd) enhances mosquito resistance to infections with fungi, bacteria and Plasmodium parasites. Here, we identify another SPH, CLIPA14, as a novel regulator of mosquito immunity. We found that CLIPA14 is a hemolymph protein that is rapidly cleaved following a systemic infection. CLIPA14 kd mosquitoes elicited a potent melanization response against Plasmodium berghei ookinetes and exhibited significantly increased resistance to Plasmodium infections as well as to systemic and oral bacterial infections. The activity of the enzyme phenoloxidase, which initiates melanin biosynthesis, dramatically increased in the hemolymph of CLIPA14 kd mosquitoes in response to systemic bacterial infections. Ookinete melanization and hemolymph phenoloxidase activity were further increased after co-silencing CLIPA14 and CLIPA2, suggesting that these two SPHs act in concert to control the melanization response. Interestingly, CLIPA14 RNAi phenotypes and its infection-induced cleavage were abolished in a TEP1 loss-of-function background. Our results suggest that a complex network of SPHs functions downstream of TEP1 to regulate the melanization reaction.